INCRETIN ANALOGUE, LIRAGLUTIDE A NEWER TREATMENT APPROACH FOR TYPE-2 DIABETES MELLITUS. - BINILA T BALAGOPAL,; SIBY JOSEPH, (International Journal of Pharma and Bio Sciences, 2013)
Glucagon-like peptide 1 (GLP-1) receptor agonists, are one among the latest addition of medication included for the management of type 2 diabetes. Liraglutide, a novel long acting glucagon-like peptide analogue, is effective at improving indices of glycemic control. It has good tolerability and safety profile. It acts in a glucose-dependent manner. In controlled trials, it was observed that it produce short –term glucose lowering effects, with the reduction of HbA1C of up to 1.3 % which is comparable with oral agents. The beneficial effects observed for liraglutide was on reduction of weight (1-3.4 kg) and blood pressure (2.1-6.7mmHg). The formation of antibodies against Liraglutide was comparatively less than that of exenatide. The effects of liraglutide on beta-cell function, cardiovascular risk and disease progression are anticipated from long-term clinical trials results. There are on-going or in development trials exploring the effects of liraglutide in prediabetes, obesity and type 1 diabetes.